The Effect of Financial Literacy, Internal Control Systems, and Accounting Information Systems on the Quality of MSME Financial Statements in Bandung City - Haifa Arrasyidah; Hj. Devyanthi Syarif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
MSMEs struggle with capital, HR, responsibility, and the law. MSME stakeholders struggle with responsibility. MSMEs are booming. However, many MSME members manually record financial transactions. Some folks also don't track their finances. The authors used quantitative descriptive and verification methods for this investigation. Bandung City has 4,309 MSME actors that embraced SAK EMKM Financial Accounting Standards. Profit and loss statements and other financial data illustrate firm performance. Financial reports list assets and responsibilities. Financial reports aid business decisions. According to their financial accounts, Bandung City MSMEs can benefit from financial literacy. Bandung City's Financial Statements' Quality the Internal Control System barely affects MSMEs. Accounting information systems improve financial statements partially. Accrual accounting, financial literacy, and internal control mechanisms improve Bandung City SMEs' financial statements